Análise de fronteiras geográficas e limites no processo temporal para avaliação de conglomerados espaço-temporais - Spencer Barbosa da Silva (2016)
Research into space-time clusters has become a subject of broad interest in scientific research. The speed of propagation of several phenomena has encouraged this interest. Particularly, associated studies with formation of clusters and spread of infectious outbreaks are quite substantial practical problems in this area. The Ffunction hasproved efficient in designing purely spatial clusters, in other hand, the purely spatial analysis has proven ineffective to overcome various situations. In practice, tools for searching simultaneously in space and start time of cluster formation are extremely valuable. It is proposed an extension to the Ffunction for the space-time problem and the introduction of a new technology capable of evaluating the intensity of possible moments of effective change in the temporal process, or to delineate a possible start time to clustering (alarm for emerging clusters). The techniques under evaluation are applied in real benchmark data, with the interest in assessing quality and compare with detection and inference mechanisms existing.